Advancement on Milk Fat Globule Membrane: Separation, Identification, and Functional Properties - Wang, Cong; Qiao, Xinyu; Gao, Zengli; Jiang, Lianzhou; Mu, Zhishen (Frontiers in Nutrition, 2022)
Dairy products have become more common in people's daily diets in recent years, and numerous useful components derived from milk are widely employed in the food industry. Milk fat globule membrane (MFGM) is a kind of film that encases milk fat globules, and has been shown to have a high nutritional value. In this work, the protein, lipid, carbohydrate, and other components of MFGM are discussed, as well as common separation, preparation and analysis technologies, physicochemical properties and functional features of MFGM are reviewed, in order to provide some guidance for the development and utilization of MFGM.